Firefighters’ biomonitoring: impact of fire combat on levels of urinary monohydroxyl metabolites of polycyclic aromatic hydrocarbons - Oliveira, M. (2018)
Firefighters, one of the most hazardous occupations, are regularly exposed to complex mixtures of pollutants during fire combat. Polycyclic aromatic hydrocarbons (PAHs) are distributed between the gaseous and particulate phases of air: they are one of the most health-relevant pollutants released during fires because of their genotoxic, mutagenic, and carcinogenic properties [1]. This work aims to assess the impact of firefighting activities on firefighters’ total exposure to PAHs. Spot urine samples were collected in healthy and non-smoking firefighters before and after fire combat activities. Six urinary PAH metabolites (1-hydroxynaphthalene (1OHNaph), 1-hydroxyacenaphthene (1OHAce), 2-hydroxyfluorene (2OHFlu), 1-hydroxyphenanthrene (1OHPhen), 1-hydroxypyrene (1OHPy), and 3-hydroxybenzo[a]pyrene (3OHB[a]P)) were quantified by liquid chromatography with fluorescence detection [2-3]. Urinary 1OHNaph and 1OHAce were the predominant biomarkers of exposure in both non-exposed and exposed firefighters, accounting with 63-98% of total levels of PAH biomarkers (ΣOH-PAHs). 2OHFlu, 1OHPhe, and 1OHPy contributed with 1-17%, 1-13%, and 0.3-10% of ΣOH-PAHs, respectively. The PAH biomarker of carcinogenicity (3OHB[a]P) was not detected. Overall exposed firefighters presented levels of ΣOH-PAHs that were 2-35% higher than for non-exposed subjects. Urinary 2OHFlu seems to be the compound with the most pronounced increments in exposed firefighters. Urinary 1OHPy levels were always lower than the benchmark of 0.5 μmol/mol creatinine proposed by the American Conference of Governmental Industrial Hygienists. More studies assessing PAH biomarkers of exposure but also biomarkers of effect and susceptibility are needed to evaluate the impact of fire emissions on the health of firefighters.